Preparation and Water-Gas Shift Performance of Zinc Oxide Supported Dispersed Gold Catalysts - Barhuizen, Andrew David (Department of Chemistry, 2024)
The classical deposition-precipitation synthesis from the group of Haruta (Tsubota eta/., 1995) -where the support is added to a pH adjusted solution of HAuCI4 and the system aged at constant pH and temperature - was examined, using ZnO as the support. Gold uptake by the support was confirmed to decrease with ageing pH, tending to zero as the IEPS of ZnO (- 9) is approached. Such behaviour is both qualitatively and quantitatively consistent with theory, which proposes that the magnitude and polarity of the charge on the support surface will determine the effective carrying capacity of that surface for an (an)ionic solution phase gold species. Decreasing post-calcination (120°C} gold crystallite size with increasing ageing pH [as reported by Haruta (1997)] was also observed (figure 11.2) - but it is not clear whether this resulted from pH dependent crystallization dynamics, from crystallite size being simply determined by the amount of deposited gold (which clearly decreases with increasing pH), or from chloride induced sintering during heat treatment (with chloride uptake by the support decreasing with increasing pH [Kung e t a /., 2003)). Nevertheless, gold deposition at pH 8 produced highly dispersed gold crystallites around 3.5 nm in diameter.